Anatomic Endodontic Technology: Listen to the needs of the tooth - E Soujanya; Chandrakanth Majeti (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Anatomic Endodontic Technology (AET) is a minimally invasive endodontic preparation system. The evolution of reciprocating AET has advanced the efficiency and predictability of the enlargement of root canal system. This new advancement utilizes stainless steel shaping files to anatomically instrument the coronal and middle third of the tooth, followed by nickel titanium files to instrument the critical zone towards the apex. It eliminates or minimizes the degree and types of procedural errors that occur during shaping.